Konstruksi Sistem Pendidikan Pesantren Tradisional di Era Global: Paradoks dan Relevansi - Purnamasari, Nia Indah (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2016)
Traditional Islamic boarding school is one of the traditional Islamic educational institutions. with the main purpose of education in it is to forming an integrated personality. Education system education system only teaches Islamic religious sciences (kitab kuning) as the core of its curriculum. (kitab kuning) as the core of its curriculum, and does not teach general knowledge. general knowledge. The pesantren curriculum is determined independently by the kiai and does not include the state curriculum. In the global era - where where the negative impact of advances in science and technology is progress is felt more by the community, especially with the emergence of various forms of moral decadence - the traditional pesantren education system is still relevant to be maintained. education system is still relevant to be maintained. Pesantren is still needed because it is able to fulfill fulfillment of human spiritual needs.